2019
DOI: 10.5604/01.3001.0012.8556
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of acute appendicitis in older patients

Abstract: Introduction Acute appendicitis (AA) is the most common indication for emergency surgery and it occurs more often in children and young adults than in patients of advanced age. AA in older patients is a challenging surgical problem because of its atypical presentation. This study was performed to determine whether the age of a patient impacts the outcomes and whether laparoscopic appendectomy (LA) is a feasible method for treatment of patients > 65 years. Material and methods We performed a retrospective st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 1 publication
0
8
0
1
Order By: Relevance
“…For the present article, the requirement for operation within the first 2 calendar dates of admission was to confirm high acuity but not necessarily an immediately life‐threatening admitting diagnosis. In addition, primary diagnoses of appendicitis, cholecystitis, and simple soft tissue abscess, although noted to contribute to the overall national burden of EGS disease given their incidence, were excluded because they are typically well tolerated by most patients including those in older age groups . Our goal in defining a group of high‐acuity diagnoses was to focus on those older individuals at highest risk of debilitating outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…For the present article, the requirement for operation within the first 2 calendar dates of admission was to confirm high acuity but not necessarily an immediately life‐threatening admitting diagnosis. In addition, primary diagnoses of appendicitis, cholecystitis, and simple soft tissue abscess, although noted to contribute to the overall national burden of EGS disease given their incidence, were excluded because they are typically well tolerated by most patients including those in older age groups . Our goal in defining a group of high‐acuity diagnoses was to focus on those older individuals at highest risk of debilitating outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…The rate of laparoscopies performed on the elderly varies significantly, ranging from 19.3% to 67% [ 12 , 31 , 46 , 51 ] depending on the year of the study (these are retrospective observational studies), but mainly depend on the preference of the surgeon.…”
Section: Treatmentmentioning
confidence: 99%
“…This increases to 7.8–11 days [ 12 , 62 ] in patients above the age of 80 as compared to 2.6–3.2 days [ 12 , 31 ] in the younger population. Some studies differentiate mean LOS in complicated appendicitis (6.5–8.3 days) [ 46 , 51 ] and uncomplicated appendicitis (3.2–3.56 days) [ 51 ].…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
“…Several recent studies about the use of minimally invasive surgical methods have demonstrated the superiority of laparoscopic surgical methods over open surgery. 6 Th e use of laparoscopic methods over open surgery is currently increasing due to reasons such as reduced postoperative pain, shorter hospital stays, shorter time to return to daily life and fewer surgical site infections. 7 Acute appendicitis is a condition that usually aff ects the young population.…”
Section: Discussionmentioning
confidence: 99%